Produção de ácido glucônico e xarope de frutose a partir de sacarose catalisada por enzimas em reator airlift - Mafra, Agnes Cristina Oliveira (2013)
The sugarcane sugar (sucrose) is a raw material produced in abundance in Brazil, being attractive to produce high added-value by-products. The gluconic acid (GA) can be obtained by multienzymatic conversion of sucrose, using three enzymes. Invertase, responsible for the inversion of sucrose to glucose and fructose, glucose oxidase (GOD) responsible for the glucose oxidation and catalase (CAT) responsible for decomposition of hydrogen peroxide. In multienzymatic process fructose is obtained as a byproduct, also of great interest to the food, pharmaceutical and chemical industries. In this study, the production of GA from sucrose in airlift reactor is evaluated. Temperature and pH of maximum activity were determined for the enzymes invertase, GOD and CAT , as well as the thermal stability in the absence of substrate. Invertase enzymatic activity was quantified by formation of reducing sugars on a 200 mM sucrose solution at 30 ° C, and pH 4.8. The enzymatic activity of GOD and the CAT were determined by monitoring respectively the formation of H2O2 from a solution of glucose 1 g/L, 25°C, pH 5.0 and the decomposition of H2O2 from a solution of H2O2 35 mM, 25°C, pH 7.5. Invertase showed maximum activity at 45 ºC and pH 5.0; GOD at 55ºC and pH 6.0 and CAT at 25 ° C and pH 8.0, respectively. From the activity profiles as a function of temperature and pH, the operational conditions of 50, 45 and 40°C at pH 5.0 and 6.0 were pre-selected for the multienzymatic process. It was found that the best half-lives times of the soluble enzymes, invertase, GOD and CAT, occurred in the condition of 40°C and pH 6.0, respectively 137, 105 and 98 h. A kinetic study was carried out at 40°C and pH 6.0. The kinetics of the enzyme invertase showed a behavior best predicted by the model of substrate inhibition. Michaelis-Menten model (MM) was fitted to experimental data of GOD and substrate inhibition model best predicted the kinetics behavior of CAT. The proposed kinetic models were used to estimate enzyme/substrate ratio (w/w) used in the production of GA in agitated and aerated and airlift bioreactors. On the other hand, in the batch assays conducted in airlift bioreactor were obtained AG real yields of 80.38 ± 5.69% and global yields of 103.20 ± 13.96% and conversion of sucrose of 98.86 ± 0.97%; obtained after 5 h. A new set of kinetic parameters including volumetric oxygen transfer coefficient (kLa) was based on the experimental data from tests in airlift bioreactor. These showed that Bi-Bi Ping-Pong model both with or without product inhibition correspond satisfactorily to the tendency of the experimental data.